How can swimmer's nutrition improve the performance: a systematic review - Cai, Y.; Zhou, C.; Huang, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Although the nutrition problems of swimmers has been well documented in the literature, still insufficient nutrition existed in swimmers. The aim of this study is therefore to explore how to deal with the problem of insufficient nutrition supplement in swimmers to improve the performance of the athletes.